Higher Platelet-to-Lymphocyte Ratio Is Associated With Worse Outcomes After Intravenous Thrombolysis in Acute Ischaemic Stroke - Xu, Jing-Han; He, Xin-Wei; Li, Qiang; Liu, Jian-Ren; Zhuang, Mei-Ting; Huang, Fei-Fei; Bao, Guan-Shui (Frontiers in Neurology, 2019)
Objective: The platelet-to-lymphocyte ratio (PLR) is a new marker of atherosclerotic inflammation and has been identified as a predictive factor in cardiovascular diseases, but its significance in patients with acute ischaemic stroke (AIS) who have undergone intravenous thrombolysis (IVT) is still unknown. Methods: Consecutive patients who were treated with IVT using recombinant tissue plasminogen activator (rtPA) for AIS were included from May 2012 to August 2018. The PLR was calculated according to platelet and lymphocyte counts within 24 hours after thrombolysis therapy. Functional outcomes were assessed by the modified Rankin Scale (mRS) at 3 months after thrombolysis. Stroke severity was assessed by National Institutes of Health Stroke Scale (NIHSS) scores. The primary endpoint was an unfavourable outcome (mRS > 2), and the secondary endpoint was death at 3 months. Results: A total of 286 patients were included in the study. The median age was 69.5 (59.0–80.0) years, and 59.1% of patients were men. A total of 120 (42.0%) patients had an unfavourable outcome, and 38 (13.2%) died. Patients with an unfavourable outcome had significantly higher PLR values compared with those with a favourable outcome (172.5 (105.3-239.0) vs 139 (97.0-194.5), P=0.008), and the PLR values of the patients who died at 3 months were higher than those of the surviving patients (189.5 (127.5-289.0) vs 142.0 (98.0-215.5), P=0.006). After adjustment for other variables, the PLR was independently associated with the two endpoints: unfavourable outcome (OR 2.220, 95% CI 1.245–3.957, P = 0.007) and death (OR 2.825, 95% CI 1.050–7.601, P = 0.040) at 3 months after thrombolysis. In addition, PLR was correlated with the NIHSS score (R = 0.230, P < 0.001). Conclusions: Higher PLR levels were independently associated with an unfavourable outcome and death at 3 months in AIS patients treated with IVT.